2018
DOI: 10.3389/fonc.2018.00616
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Cetuximab-Induced Skin Toxicity in Recurrent or Metastatic Squamous Cell Carcinoma of the Head and NECK

Abstract: Background: Skin toxicity is a common adverse event during cetuximab (Cmab) treatment. However, few reports have investigated the correlation between skin toxicity and the efficacy of Cmab in patients with recurrent or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN).Methods: We retrospectively reviewed 112 R/M SCCHN patients who received palliative chemotherapy with Cmab. Main eligibility criteria included primary disease in the oral cavity, hypopharynx, nasopharynx, oropharynx, or larynx; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Common adverse events. PFS of 3.9-7.7 months, and median OS of 7.6-16.8 months(8)(9)(10)(11)(12)(13)(14)(15)(16). The results of our study are consistent with those of previous studies.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Common adverse events. PFS of 3.9-7.7 months, and median OS of 7.6-16.8 months(8)(9)(10)(11)(12)(13)(14)(15)(16). The results of our study are consistent with those of previous studies.…”
supporting
confidence: 92%
“…Recently, the combination of taxanes and Cmab, for example, exchanging 5-FU for taxanes in the Extreme regimen, has drawn attention (7). Cmab and paclitaxel combination therapy (Cmab-PTX), first reported by Hitt et al (8), is one such combination, and some studies have reported that Cmab-PTX has good efficacy for R/MHNSCC patients (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). However, the prognostic factors associated with Cmab-PTX have been inadequately reported (9,10).…”
mentioning
confidence: 99%
“…15,16 However, occurrence of more severe Cmabinduced skin toxicity is correlated with better treatment response and longer survival in several studies across multiple malignancies. 12,17,18 Cmab therapy should be continued if it has a therapeutic effect. Therefore, it is important to manage skin toxicities such as paronychia and skin fissures because treatment interruption and discontinuation due to the severity of skin toxicity should be avoided in order to achieve maximum benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Survival was computed from the landmark (39). Similarly an analysis of the predictive value of cetuximab-induced skin toxicity in recurrent or metastatic head and neck cancer was conducted using the landmark method applied to PFS and OS counted from 90 days after the start of therapy (40).…”
Section: The Specificities Of Head and Neck Cancer And Statistical Comentioning
confidence: 99%